2014
DOI: 10.1186/1471-2164-15-479
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of Riemerella anatipestifer reveals genetic diversity

Abstract: BackgroundRiemerella anatipestifer is one of the most important pathogens of ducks. However, the molecular mechanisms of R. anatipestifer infection are poorly understood. In particular, the lack of genomic information from a variety of R. anatipestifer strains has proved severely limiting.ResultsIn this study, we present the complete genomes of two R. anatipestifer strains, RA-CH-1 (2,309,519 bp, Genbank accession CP003787) and RA-CH-2 (2,166,321 bp, Genbank accession CP004020). Both strains are from isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 46 publications
0
41
0
Order By: Relevance
“…Virulence evaluation of different R. anatipestifer isolates in ducklings and G. mellonella larvae. The degrees of virulence of two different R. anatipestifer isolates, R. anatipestifer ATCC 11845 and R. anatipestifer CH-1 (28), were first assessed in the duckling infection model. As Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Virulence evaluation of different R. anatipestifer isolates in ducklings and G. mellonella larvae. The degrees of virulence of two different R. anatipestifer isolates, R. anatipestifer ATCC 11845 and R. anatipestifer CH-1 (28), were first assessed in the duckling infection model. As Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These previous results suggested that TonB-dependent pathways may play important roles in R. anatipestifer iron acquisition. According to the full genome sequences of four R. anatipestifer strains in GenBank, this bacterium is predicted to contain two TonB-ExbB-ExbD systems (Mavromatis et al, 2011;Wang et al, 2014;Yuan et al, 2011). In this study, by deleting the tonB1 or tonB2 gene from R. anatipestifer strain CH3, the roles of the two TonB proteins in haemin iron acquisition and pathogenesis were investigated.…”
Section: Introductionmentioning
confidence: 98%
“…Among them, serotypes 1, 2, 3, 5, and 15 are the major pathogens affecting the duck industry. No cross protection has been found among these serotypes56. RA infection produces mortality and morbidity rates ranging between 10 and 30%, but mortality rates as high as 75% have been reported in infected duck farms7.…”
mentioning
confidence: 99%